Are There Levels of Consciousness?. Issue 6 (June 2016) - Bayne, Tim; Hohwy, Jakob; Owen, Adrian M.
Abstract : The notion of a level of consciousness is a key construct in the science of consciousness. Not only is the term employed to describe the global states of consciousness that are associated with post-comatose disorders, epileptic absence seizures, anaesthesia, and sleep, it plays an increasingly influential role in theoretical and methodological contexts. However, it is far from clear what precisely a level of consciousness is supposed to be. This paper argues that the levels-based framework for conceptualizing global states of consciousness is untenable and develops in its place a multidimensional account of global states. Trends: The notion of a conscious level plays an increasingly important role in the science of consciousness, but there has been little conceptual analysis of the notion and it is typically left unexplained. The standard conception of conscious levels identifies them with changes in a creature's degree of consciousness, but this conception is theoretically problematic and fails to do justice to the multifaceted nature of levels. Global states of consciousness are multidimensional phenomena that capture the cognitive and behavioural dimensions of consciousness, such as the ways in which conscious contents are gated and their functional roles.